2005
DOI: 10.1002/adfm.200400454
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Effects of Nanoscale Architecture on the Mechanical Properties of Hexagonal Silica/Polymer Composite Thin Films

Abstract: We examine the effects of controlling nanoscale architecture on the tensile properties of honeycomb‐structured silica/polymer composite films. The hexagonal films are produced using evaporation‐induced self‐assembly and uniaxially strained using a home‐built tensile testing apparatus. Significant differences in the yield strain, failure strain, and tensile moduli between the axes parallel and perpendicular to the film‐deposition direction are observed for the thinnest films examined and are attributed to aniso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…[23][24][25] Moreover, previous reports on templated oxide materials demonstrated that the ordered porous architecture also provides additional mechanical flexibility, which facilitates volume variations during cycling. [24,26] Conventionally, carbon materials with ordered porous structures, such as CMK-3, are synthesized by the ordered porous hard template-assisted nanocasting method, which produces an inverse porous structure. [27,28] Multiple steps, including impregnation of the carbon source, carbonization, and template removal, are required to obtain the ordered structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25] Moreover, previous reports on templated oxide materials demonstrated that the ordered porous architecture also provides additional mechanical flexibility, which facilitates volume variations during cycling. [24,26] Conventionally, carbon materials with ordered porous structures, such as CMK-3, are synthesized by the ordered porous hard template-assisted nanocasting method, which produces an inverse porous structure. [27,28] Multiple steps, including impregnation of the carbon source, carbonization, and template removal, are required to obtain the ordered structure.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the ordered structure, in particular, improves the rate performance of electrochemical energy storage devices, such as Li/Na‐ion batteries, supercapacitors, and Li–S batteries . Moreover, previous reports on templated oxide materials demonstrated that the ordered porous architecture also provides additional mechanical flexibility, which facilitates volume variations during cycling …”
Section: Introductionmentioning
confidence: 99%
“…Thus, upon treatment with small bidentate ligands, there should be negligible volume contraction. The flexibility of nanoporous networks is also likely to help accommodate any volume change that does occur upon cross-linking …”
Section: Introductionmentioning
confidence: 99%
“…The combination of the properties of a polymeric matrix and silica makes them attractive as barrier, optical, constructional, and other materials. The methods available for the preparation of the polymer–silica nanocomposites are based on the incorporation of nanoparticles of natural foliated or synthetic silica into a matrix by mixing them with a polymer melt or solution, the successive synthesis of a polymer or silica, or their simultaneous synthesis, with silica being obtained by the sol–gel method. In addition, there are some exotic approaches, such as silica precipitation in polymer plasma …”
Section: Introductionmentioning
confidence: 99%